2019
DOI: 10.1186/s12985-019-1148-2
|View full text |Cite|
|
Sign up to set email alerts
|

Piscine orthoreovirus sequences in escaped farmed Atlantic salmon in Washington and British Columbia

Abstract: Background Piscine orthoreovirus (PRV) is an emergent virus in salmon aquaculture belonging to the family Reoviridae . PRV is associated with a growing list of pathological conditions including heart and skeletal inflammation (HSMI) of farmed Atlantic salmon. Despite widespread PRV infection in commercially farmed Atlantic salmon, information on PRV prevalence and on the genetic sequence variation of PRV in Atlantic salmon on the north Pacific Coast is limited. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 37 publications
(67 reference statements)
1
18
0
Order By: Relevance
“…These authors suggested that the grouping of PRV-1 into sub-genogroups 1a and 1 b did not adequately describe the genetic patterns in their larger dataset. Kibenge et al. (2019) reported separation of sequences into the two genogroups 1a and 1 b, with sequences from the northeast Pacific grouping with sequences from Iceland, Norway, and Chile within 1a.…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested that the grouping of PRV-1 into sub-genogroups 1a and 1 b did not adequately describe the genetic patterns in their larger dataset. Kibenge et al. (2019) reported separation of sequences into the two genogroups 1a and 1 b, with sequences from the northeast Pacific grouping with sequences from Iceland, Norway, and Chile within 1a.…”
Section: Introductionmentioning
confidence: 99%
“…PRV-1 S1 sequences from both aquaculture escapees differed from those isolated from wild fish at sea (Greenland-collected), and PRV-1 was not detected in either wild river-sampled population in this study. It is worth noting that the PRV-1 variants observed both in Greenland and in eastern Canada all clustered with the Norwegian "wild-type" variant, classified in some studies as PRV-1a (Kibenge et al 2019) that, based on the S1 segment, is divergent from PRV-1b, has been proposed to be of higher virulence (Dhamotharan et al 2019) and has been shown to be the causative agent of heart and skeletal muscle inflammation (HSMI) (Wessel et al 2017). However, HSMI has been diagnosed in farmed Atlantic salmon in western Canada in association with PRV-1a (Di Cicco et al 2017).…”
Section: Marine Transmission Potential Between Continental Stocksmentioning
confidence: 98%
“…The initial genome naming and annotation of PRV proposed that L1, L2, L3, M1, M2, M3, S1, S2, S3 and S4 segments code for the λ1, λ2, λ3, μ2, μ1, μNS, σ3/p13, σ2, σNS and σ1 proteins, respectively (Palacios et al., 2010). This scheme was followed by Kibenge et al (2013) when establishing the first PRV genome in GenBank (GCA_002829625.1) and has been followed by a number of subsequent researchers (Di Cicco et al., 2017; Kibenge et al., 2019; Polinski, Marty, Snyman, & Garver, 2019; Takano et al., 2016). However, one early study reversed the naming of L1 and L3 so that the term L1 would be used to identify the segment that codes λ3, similar to the terminology applied to an analog, mammalian orthoreovirus (MRV) (Markussen et al., 2013).…”
Section: Biologymentioning
confidence: 99%
“…Current data suggest that this was a result of a single introduction prior to 1987 (Siah et al, in press ). A second introduction of PRV‐1a via importation of Atlantic Salmon into Washington state from Iceland appears to have occurred within the last decade (Kibenge et al., 2019; Siah et al, in press ); however, it is as yet unclear if this introduction will result in regional establishment of this second PRV‐1a variant in the North Pacific. PRV‐1 is also hypothesized to have been introduced to Chile from both North Pacific and North Atlantic sources, possibly in multiple introduction events (Siah et al, in press ).…”
Section: Biologymentioning
confidence: 99%
See 1 more Smart Citation